Bioactivator Based On Organic Waste for Maggot Media - Yunilas; N. Ginting; N. Saidi; Tarigan, E. (Talenta Publisher, 2022)
Bioactivator is needed for making maggot growth media. This study aims to determine the quality of bioactivator based on various organic waste. The research design used was a 4x3 factorial randomized design (CRD) with three replications. The factor I was various organic wastes (D1 = vegetable waste, D2 = fruit waste, D3 = food processing waste, D4 ​​= mixed waste and Factor II was length of fermentation day (L1 = 7 days, L2 = 14 days, L4 = 21 days), the variables observed were pH, colour, aroma, microbial population, and total acid. pH of media was in the range of 5.4 - 6.7. There was no difference in colour and aroma due to each treatment. Population of microbial in the range of 11.36 x 105 - 2.18 x 106, 14 days fermentation caused highest microbial population. Total acid range of 2.21 - 3.15. In conclusion bioactivator of vegetable, fruit, food processing and mixed waste almost has the same characteristics on pH, colour, aroma and total acid. However, 14 days of fermentation produced better bioactivator. This study will be continued with the application of bioactivators as maggot media growth.